PENYELENGGARAAN PELAYANAN PUBLIK DALAMPEMBUATAN E-KTP DI KANTOR KECAMATAN TEKARANG KABUPATEN SAMBAS - Rizky Darmawan E.42009002 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
The purpose of this essay is to describe and analyze standard of public service in Tekarang Subdistrict office in making of E-KTP and yet completed public service standard so it unappropriate with public expectations. The tittle of this essay was appointed by the problem that standard of public service has not been completed. This research uses qualitative approach with descriptive study. Techniques of data collection is observation field researchers to obtain data directly, documentation study, interviews with informants who were directly involved in the making of E-KTP. Location of this research in Tekarang Subdistrict Sambas Regency. Subjects of this research are Head of Tekarang Subdistrict Office, goverment section, recorder officer of E-KTP and people in Tekarang Regency. The result of this research were found the facts such as tangible dimentions : appearance of public service personnels in making of E-KTP yet neat, peoples are not comfortable in doing service, dicipline of public service personnels has been good enough, and damaged E-KTP recorders. Realibility dimentions : personnels accuracy in the making of E-KTP has good enough, Service standars are not yet clear, personnels skill and ability in using tools is good. For responsiveness dimensions: responding officers had any people who want to make the E-KTP, which is not very fast service, serving the community with precise and meticulous, and yet collected public complaints due to suggestion no complaints. For empathy dimension of service personnels already serving with friendly, polite and non-discriminatory. Keyword : Standard, Service, Public, E-KTP